Multiple Temporal‐Scale Photocarrier Dynamics Induced by Synergistic Effects of Fluorination and Chlorination in Highly Efficient Nonfullerene Organic Solar Cells. Issue 4 (3rd April 2020) - Zhang, Kang-Ning; Niu, Meng-Si; Jiang, Zhi-Nan; Chen, Zhi-Hao; Wang, Tong; Wei, Meng-Meng; Qin, Chao-Chao; Feng, Lin; Qin, Wei; So, Shu-Kong; Hao, Xiao-Tao
Abstract : Nonfullerene Organic Solar Cells In article number 1900552, Chao‐Chao Qin, Xiao‐Tao Hao, and co‐workers investigate the influence of the synergetic effects of fluorination and chlorination on multiple temporal‐scale photocarrier dynamics based on a 2 × 2 matrix of organic solar cells. Both fluorination and chlorination have a positive effect on exciton diffusion, exciton dissociation, charge carrier transport, and collection, contributing to the enhancement of photovoltaic performance.